Realita Kapasitas Pesantren Di Kota Palu - Sofyan Sofyan (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
Pesantren Capacity Mapping Research in Central Sulawesi, one of which wasconducted in Palu City to all pesantren in Palu City. Using descriptive method. Theresearch aims to map out the distribution of pesantren, the main elements inpesantren, including kiai, pengajian kitabi, santri, mushalla / mosque, and dormitory,as well as on empowering and planting national values. The study found thatpesantren has not spread to all sub-districts. The five main elements that are expectedto be owned by pesantren are only owned by some pesantren. Empowerment andcultivation of national values, also has not been optimized, because the network isneeded cross-boarding and intense coordination of the Ministry of Religious Palu